A217 NONINVASIVE ASSESSMENTS TO IDENTIFY PATIENTS WITH ADVANCED FIBROSIS DUE TO NASH: SCREENED POPULATION FROM THE REGENERATE TRIAL. (4th March 2021) - Montano-Loza, A J; Boursier, J; Sanyal, A J; Ratziu, V; Rinella, M; Loomba, R; Dufour, J; Mozaffari, E; Shringarpure, R; MacConell, L; Granston, T; Zhou, H; et al.
Abstract: Aims: We explored the ability of noninvasive tests (NITs) to identify patients (pts) with advanced fibrosis due to NASH. Methods: All screened pts from the ongoing phase 3 REGENERATE with available histology data were included. Five NITs were evaluated using established literature cutoffs to identify or exclude advanced fibrosis (values between upper and lower thresholds were considered indeterminate): Aspartate Transaminase-to-Platelet Ratio Index (APRI; ≥0.57, ≤0.84), Enhanced Liver Fibrosis (ELF; ≥7.7, <9.8), Fibrosis-4 (FIB-4; ≥1.30, <2.67), NAFLD fibrosis score (NFS; ≥−1.455, <0.676), and Transient Elastography (TE; ≥7.9 kPa, <9.6 kPa). Three testing methods applied were single NIT, 2 simultaneous NITs weighted equally (NFS+ELF, FIB-4+ELF, NFS+TE, FIB-4+TE), and 2 sequential NITs with the second test performed only if the first test was indeterminate (NFS→ELF, FIB-4→ELF, NFS→TE, FIB-4→TE). Results: 4133 pts in the REGENERATE screened population had an available biopsy (baseline liver biopsy: F0, 15.5%; F1, 27.2%; F2, 21.2%; F3, 29.6%; F4, 6.5%). Of these, 96% had FIB-4, NFS, and APRI, 41% had TE, and 28% had ELF. Single NITs with upper thresholds demonstrating strong specificity for identification of advanced fibrosis were FIB-4 (97%), NFS (94%), and APRI (86%); NITs with lower thresholds demonstrating good sensitivity for identification of early fibrosis were ELF (100%) and TE (88%). Evaluation of 2 simultaneous NITs resulted in a greater percentage of pts in the indeterminate zone. Application of 2 sequential tests improved the accuracy of identification and reduced misclassification vs 2 simultaneous tests. Conclusions: Sequential NIT strategies may decrease liver biopsy rates while maintaining the accuracy of noninvasive diagnosis in pts with advanced fibrosis due to NASH. Funding Agencies: Intercept Pharmaceuticals